The anti-proliferative effects of adiponectin on human lung adenocarcinoma A549 cells and oxidative stress involvement. (April 2019) - Nigro, E.; Stiuso, P.; Matera, M.G.; Monaco, M.L.; Caraglia, M.; Maniscalco, M.; Perrotta, F.; Mazzarella, G.; Daniele, A.; Bianco, A.
Abstract: Adiponectin (Acrp30) plays an important role in energy metabolism and inflammation. Recently, in vivo serum Acrp30 levels have been reported to be correlated to risk of developing several types of cancers such as lung cancer, and in vitro studies have demonstrated a role for Acrp30 in the control of cell proliferation and survival. However, the molecular effects of Acrp30 on lung cancer have not yet been clearly defined. In the present study, we investigated the effects of different concentrations of Acrp30 on the A549 human alveolar epithelial cell line, an in vitro model of lung adenocarcinoma. A549 cells were exposed to various concentrations of Acrp30 and successively, proliferation, apoptosis and oxidative stress were evaluated by MTT test, caspase activity assay, flow-cytometry and western blotting analysis. Our results demonstrated that Acrp30 causes, in a time- and dose-dependent manner, a reduction of cell viability and duplication together with an increase in cell apoptosis rate. In addition, we found that Acrp30 induces an increase of lipid peroxidation evaluated by TBARS assay and a concomitant reduction of nitric oxide release, both markers of cellular oxidative stress. Taken together, our data on A549 cells provides new insight into potential involvement of Acrp30 on physio-pathologic mechanisms of lung diseases through interference with proliferation, apoptosis and oxidative status.